Media ethics : issues and cases - Wilkins, Lee; Painter, Chad, 1977-; Patterson, Philip (Lanham Rowman and Littlefield, 2022)
"The tenth edition of 'Media Ethics: Issues and Cases' has been updated with the most pressing media issues of the past two years, including coverage of the 2020 pandemic and election. This authoritative case book gives students the tools to make ethical decisions in an increasingly complex environment"--
Includes bibliographical references (pages 363-382) and index.
Keywords: Mass media -- Moral and ethical aspects; Communication -- Moral and ethical aspects